Translation and content validation of Bahasa Malaysia version of the food insecurity experience scale (FIES) - Mat Ya, Roselawati; Mohd Abu Bakar, Wan Azdie; Ab Rahman, Jamalludin; Sulaiman, Norhasmah (Malaysian Medical Association, 2019)
INTRODUCTION: Food insecurity can be defined as the limited or uncertain availability of nutritionally adequate, safe foods or the inability to acquire foods in socially unacceptable ways. Food insecurity is recognized as a public health issue worldwide where it is clearly described under the Sustainable Development Goals (SDGs) number 2: End hunger and achieve food security. To understand the complexity, multifaceted nature of food insecurity in Malaysia needs established tool and adequate data. This study aimed to translate and validate the English version of Food Insecurity Experience Scale (FIES) into Bahasa Melayu (BM) by adopting the guideline of the World Health Organization (WHO) on questionnaire translation. METHODS Two forward and backward translations involving experts in food insecurity study and experts in language were done as stipulated in a guideline. Content validity by the experts and face validity by the target population were conducted as part of validation process. RESULT Content Validity Index (CVI) and FactorialValidity Index (FVI) was done to analyses content validity. RESULTS The harmonized BM version of FIES was produced with 100% CVI. However, FVI was inconsistent. Hence a factor analysis should be done to asses the full degree of FVI. CONCLUSION The full validation study of BM version FIES especially construct and criterion validity needed to be done before it is widely used to measure food insecurity in the population specifically Malaysian population.